Visfatin Levels in Prepubertal Children Born Small or Large for Gestational Age - Giapros, V. I.; Kiortsis, D. N.; Evagelidou, E. N.; Challa, A. S.; Cholevas, V. K.; Siomou, E. C.; Bairaktari, E. T.; Andronikou, S. K. (Hormone and Metabolic Research, 2012)
Children born small (SGA) or large (LGA) for gestational age are prone to develop insulin resistance (IR) during childhood. Visfatin, a hormone with insulin-mimetic actions, has been associated with IR. This study was designed to examine whether serum level of visfatin is correlated with metabolic indices of IR, in prepuberty in association with the intrauterine growth pattern. The following parameters were evaluated at a mean age of 6.5±1.2 years in 155 prepubertal children born appropriate for the gestational age (AGA) (n=63), or SGA (n=42), or LGA (n=50): serum levels of visfatin, adiponectin, leptin, fasting glucose (GF) and insulin (IF), the homeostasis model assessment IR index (HOMA-IR), plasma lipids, anthropometric indices at birth and the time of evaluation, and obesity indices [waist circumference (WC), body mass index (BMI) and skinfold thickness]. The mean serum level of visfatin was lower in the SGA than in the AGA and the LGA children (9±5.2 vs. 11.8±5.1 and 12.7±5.6 ng/ml, respectively, p<0.01). Girls had lower visfatin levels than boys (10.4±4.3 ng/ml vs. 12.5±6.7 ng/ml, p<0.05). Visfatin was not correlated with IR indices. In multiple regression analysis visfatin level was positively correlated with birth weight z-score (t=2.56, beta=0.24, p<0.01) and crown to heel z-score (t=2.46, beta=0.22, p=0.014), independent of age, gender, maternal weight before pregnancy, maternal weight gain during pregnancy, BMI z-score, WC z-score, serum leptin and adiponectin, and HOMA-IR. In conclusion serum visfatin level was lower in prepubertal SGA children but not correlated with IR indices. Low birth weight was an independent predictor of visfatin level.
Keywords: visfatin; insulin resistance; fetal growth; obesity; birth weight